A heartbreaking work of staggering genius - Eggers, Dave (New York : Vintage Books, 2001)
A memoir of a college senior who, in the space of five weeks, loses both of his parents to cancer and inherits his eight-year-old brother. Here is an exhilarating debut that manages to be simultaneously hilarious and wildly inventive as well as a deeply heartfelt story of the love that holds a family together.
Addendum bound upside down.
Contains additional work, with added title page: Mistakes we knew were making.
Keywords: Eggers, Dave; Parents -- Death -- Psychological aspects; Brothers -- Biography